Influence of Financial Development on Environmental Quality: Research Results from Developing Countries - Nguyen, Yen; Le, Son; Ngo, Nam; Nguyen, Huyen (International Journal of Energy Economics and Policy, 2024)
This study provides evidence supporting the hypothesis that financial development reduces environmental pollution in developing countries. using an annual dataset of carbon emissions, financial development, and other factors from 1990 to 2020, with the GMM approach, We find that the more developed the financial system, the more advantageous it is for the environment. This conclusion is strengthened when particular facets of financial development are taken into account. Moreover, the impact is also influenced by the countries' wealth levels, in which countries with high average incomes have financial development that has an impact on reducing environmental pollution and the opposite result when viewed. considered in low-middle-income countries. Finally, we offer some policy recommendations regarding financial development to enhance its efficacy in maintaining environmental quality.